Autism spectrum disorder and early motor abnormalities: Connected or coincidental companions?. (January 2017) - Setoh, Peipei; Marschik, Peter B.; Einspieler, Christa; Esposito, Gianluca
Abstract: Research in the past decade has produced a growing body of evidence showing that motor abnormalities in individuals with autism spectrum disorder (ASD) are the rule rather than the exception. The paper by Chinello and colleagues furthers our understanding of the importance of studying motor functions in ASD by testing a non-clinical population of parents-infant triads. Chinello and colleagues' findings seem to suggest that subclinical motor impairments may exist in the typical population with inherited non-clinical ASD traits. Chinello and colleagues' discovery also urges us to ask why motor abnormalities exist in typically developing infants when their parents present some subclinical ASD traits. We believe that there are at least two possibilities. In the first possible scenario, motor impairments and ASD traits form a single cluster of symptoms unique to a subgroup of individuals with autism. A second possible scenario is that motor atypicalities are the first warning signs of vulnerability often associated with atypical development. In conclusion, Chinello et al.'s findings inform us that subclinical atypical phenotypes such as sociocommunicative anomalies may be related to subclinical motor performances in the next generation. This adds to our knowledge by shedding some light on the relation of vulnerability in one domain with vulnerability in another domain.